The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.2134/agronj1987.00021962007900030032x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Biological Nitrogen Fixation Associated with 11 Ecotypes of Panicum maximum Grown in Nitrogen‐15‐labeled Soil1

Abstract: Contributions of plant-associated biological nitrogen fixation (BNF) may be important to N nutrition of grass~s. Eleven ecotypes of Panicum maximum were planted in the field in concrete cylinders containing soil (Typic Hapludult) that had a low but stable ' 5 N enrichment. Brachiaria radicans (cv. IRI 442) was used as the non-fixing control, and the plant aerial tissue was harvested eight times over a 390-day period. At the first harvest of the experiment (17 May 1984), the concentration of N in all the grasse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

1987
1987
2009
2009

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 17 publications
0
20
0
1
Order By: Relevance
“…However, the presence of N 2 fi xing bacteria of the genus Herbaspirillum inside this grass, detected by Kirchhof et al (2001), reinforces the possibility that BNF is an important process to the survival and productivity of this species. The importance of BNF to other grass species was already shown, with contributions of BNF of 30 to 40% registered for Brachiaria (Boddey & Victoria, 1986) and ecotypes of Panicum maximum (Miranda & Boddey, 1987), respectively. In sugarcane, Urquiaga et al (1992) found BNF could contribute up to 70% of the plant N needs, but the expected contribution of this process for sugarcane growing in farmer fi elds are of the order of 30%, ranging from 0 to 60% (Boddey et al, 2001).…”
Section: Resultsmentioning
confidence: 82%
“…However, the presence of N 2 fi xing bacteria of the genus Herbaspirillum inside this grass, detected by Kirchhof et al (2001), reinforces the possibility that BNF is an important process to the survival and productivity of this species. The importance of BNF to other grass species was already shown, with contributions of BNF of 30 to 40% registered for Brachiaria (Boddey & Victoria, 1986) and ecotypes of Panicum maximum (Miranda & Boddey, 1987), respectively. In sugarcane, Urquiaga et al (1992) found BNF could contribute up to 70% of the plant N needs, but the expected contribution of this process for sugarcane growing in farmer fi elds are of the order of 30%, ranging from 0 to 60% (Boddey et al, 2001).…”
Section: Resultsmentioning
confidence: 82%
“…This constitutes strong evidence that there were negligible spatial or temporal variations of ''N enrichment of the mineral N pool during the 3 months of plant grow-th, as w-ould be expected, since all the soils had been labelled for more than 3 yr (Kohl & Shearer, 1981;Boddey & Victoria, 1986;Miranda & Boddey, 1987).…”
Section: Discussionmentioning
confidence: 58%
“…The '"N enrichment of the soil mineral N of such soils should be virtually stable with time (Kohl & Shearer, 1981;Boddey & Victoria, 1986;Miranda & Boddey, 1987),…”
Section: Introductionmentioning
confidence: 99%
“…Enrichment may be achieved in many ways; as additions of labelled fertilizer or organic matter (Chalk, 1985;Rennie, 1986) or soil may be used which has a stable residual ~SN label resulting from previous studies (Kohl and Shearer, 1981;Miranda and Boddey, 1987). The assumption is made that the control and test crops remove from the soil nitrogen containing the same ratio of labelled fertilizer N to non-labelled soil N even though the quantities of N derived from the soil plus fertilizer may be different.…”
mentioning
confidence: 99%
“…In the case where the 15N enrichment in the plant-available N is constant with depth and does not change with time (Kohl and Shearer, 1981;Miranda and Boddey, 1987) the two crops cannot differ in the ratio R even if they recover different quantities of 15N-enriched nitrogen. However, the common (and often the most practical) method of adding 15N as soluble fertilizer does result in large variations of ~SN enrichment with both depth (Boddey and Victoria, 1986) and time (Fried et al, 1983;Witty, 1983;Witty and Ritz, 1984).…”
mentioning
confidence: 99%